2022
DOI: 10.1101/2022.08.15.22278795
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rare variants found in clinical gene panels illuminate the genetic and allelic architecture of orofacial clefting

Abstract: Orofacial clefts (OFCs) are common craniofacial birth defects including cleft lip (CL), cleft lip with cleft palate (CLP), and cleft palate (CP). The etiological heterogeneity of OFCs complicates clinical diagnostics as it is not always readily apparent if the cause is Mendelian, environmental, or multifactorial. Although sequencing could aid diagnosis, it is not commonly used for the 60-70% of OFC cases that appear isolated or lack a strong family history. We aimed to estimate the diagnostic yield evaluating … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 79 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…We and others demonstrated that Esrp1 and Esrp2 regulate the alternative splicing of Ctnnd1, generating isoforms that differ between epithelial and mesenchymal cell types (20, 60, 66, 73), making Ctnnd1 an interesting Esrp1/2 target that has also been implicated in CL/P (61).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…We and others demonstrated that Esrp1 and Esrp2 regulate the alternative splicing of Ctnnd1, generating isoforms that differ between epithelial and mesenchymal cell types (20, 60, 66, 73), making Ctnnd1 an interesting Esrp1/2 target that has also been implicated in CL/P (61).…”
Section: Resultsmentioning
confidence: 96%
“…Pathogenic variants in CTNND1 accounted for 0.8% of the cohort. Only 10% of the cohort had a pathogenic variant in 500 genes implicated in OFC that we analyzed, making CTNND1 the mostly frequently mutated variant in this cohort (61). In the gene-based burden test, rare variants were nominally over-transmitted to affected children (p=0.06); de novo variants are enriched in CTNND1 (p=0.005 for loss-of-function de novo variants; 0.001 for protein-altering de novo variants).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For models considering variants in OFC genes, we utilized a gene list comprised of 418 genes previously associated with craniofacial development and OFCs. These were compiled from four sources, including OMIM (Amberger et al, 2015), the PreventionGenetics Cleft Lip/Cleft Palate Panel (PreventionGenetics, Marshfield, WI), the Genomics England PanelApp Clefting Panel (v2.2, March 2020; (Martin et al, 2019)), and an additional set of literature-curated genes (more information on this gene list can be found in Diaz Perez et al (2022). We considered a significance level for both the “all genes” and “OFC genes” at P < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…OMIM clinical synopses search terms included: “cleft lip,” “cleft palate,” “oral cleft,” “orofacial cleft,” and “cleft lip and/or palate;”, (b) the PreventionGenetics Cleft Lip/Cleft Palate clinical genetic testing panel (PreventionGenetics, Marshfield, WI), (c) the Genomics England PanelApp cleft panel (v2.2), an expert‐curated list of genes for familial cleft lip and/or cleft palate, familial isolated clefting, and syndromic clefting (Martin et al, 2019), and (d) literature‐curated genes. More information on this gene list can be found in Diaz Perez et al (2023). For the mixed model analyses, we considered a significance level for both the “all genes” and “OFC genes” at p < 0.05.…”
Section: Methodsmentioning
confidence: 99%